Polariton condensation with localized excitons and propagating photons - EASTHAM, PAUL (American Physical Society, 2004)
We estimate the condensation temperature for microcavity polaritons, allowing for their internal structure. We consider polaritons formed from localized excitons in a planar microcavity, using a generalized Dicke model. At low densities, we find a condensation temperature Tc / , as expected for a gas of structureless polaritons. However, as Tc becomes of the order of the Rabi splitting, the structure of the polaritons becomes relevant, and the condensation temperature is that of a BCS-like mean-field theory.We also calculate the excitation spectrum, which is related to observable quantities such as the luminescence and absorption spectra.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; polaritons